Efeito da variação de frequência e duração do estímulo no registro do P300 e MMN - Gução, Ana Cláudia Bianco [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Introduction: The Cognitive Potential (CP) test refers to the picking up of specific electric events that evoke sensory responses of the brain from external stimuli. CPs are composed of N1, P2, N2, P3 and MMN components, which reflect the integrity and neuromaturational state of the auditory pathway in children, specifically auditory cortical abilities such as attention, discrimination, memory and brain integrity. This test, applied in children with typical development, is of great value, since these normative data will assist in understanding alterations in children's language and learning linked to attention deficits and auditory memory and cognition. Objective: To investigate the effect of frequency variation and duration on Cognitive Potentials (CPs) in children with typical development. Materials and Methods: 50 subjects (27 males and 23 females) aged 8-12 years and 11 months who attended private and public schools in Marilia and had good academic performance. These individuals were divided into two groups according to age: one group with 8 to10 years 11 months children and the other with 11 to12 years 11 months children. As inclusion criteria, we admitted subjects without neurological, psychiatric or motor impairments, according to the history answered by parents and hearing acuity within normal standards according to audiological evaluation. Cognitive potential, P300 and its other components and MMN were performed, differing in frequency and duration, measured at right and left. Data analysis was carried out using descriptive statistics of mean, standard deviation, minimum and maximum. Following, comparative analyzes were made between the variations of frequency versus duration for each component using the Student T Test as well as correlation of frequency and duration measures through Pearson Correlation Test for P300 and its other components and MMN. Results: It was observed that the discrimination of frequency produced alteration...

Introdução: O teste dos potenciais cognitivos (PC) se refere à captação de eventos elétricos específicos que evocam respostas sensoriais do cérebro a partir de estímulos externos. Os PCs são compostos pelos componentes N1, P2, N2, P3 e MMN, que refletem a integridade e o estado neuromaturacional da via auditiva em crianças, refletindo habilidades corticais auditivas como atenção, discriminação, memória e integridade do cérebro. Esse teste aplicado na população infantil com desenvolvimento típico é de grande valor, uma vez que esses dados normativos auxiliarão na compreensão das alterações infantis na linguagem e aprendizagem, ligados a déficits de atenção e memória auditiva e cognição. Objetivo: investigar o efeito da variação da frequência e duração nos Potenciais Cognitivos (PCs) em crianças com desenvolvimento típico. Materiais e Métodos: participaram deste estudo 50 indivíduos de ambos os gêneros na faixa etária de 8 a 12 anos e 11 meses, composto por 27 do gênero masculino e 23 do feminino, os quais frequentavam escolas particulares e públicas em Marília e apresentavam bom desempenho acadêmico. Esses indivíduos foram divididos em dois grupos, que diferiam quanto à idade, sendo um grupo de 8 a 10 anos e 11 meses e outro de 11 a 12 anos e 11 meses. Como critérios de inclusão, eram indivíduos sem comprometimentos neurológicos, motores ou psiquiátricos de acordo com a anamnese respondida pelos pais e acuidade auditiva dentro dos padrões da normalidade segundo avaliação audiológica. Foi realizado o teste dos PCs, na discriminação de frequência e duração, aferido à direita e esquerda. Os dados foram analisados pela estatística descritiva da média, desvio padrão, mínimo e máximo. Na sequência, foram feitas análises comparativas entre as variações de frequência versus duração para cada componente com o Test T de Student, além...
Keywords: Potenciais auditivos evocados; Desenvolvimento cognitivo; Crianças; Percepção auditiva; Auditory perception